The amino-terminal domain of the transcription termination factor TTF-I causes protein oligomerization and inhibition of DNA binding. - Sander, E E (1996)
The transcription termination factor TTF-I binds specifically to an 18 bp DNA element in the murine ribosomal gene spacer and mediates termination of RNA polymerase I transcription. In this study, we have compared DNA binding and termination activity of recombinant full-length TTF-I (TTF-Ip130) with two deletion mutants lacking 184 and 322 N-terminal amino acids, respectively. All three proteins exhibit similar termination activity, but the DNA binding of TTF-Ip130 is at least one order of magnitude lower than that of the deletion mutants, indicating that the N-terminus represses the interaction of TTF-I with DNA. The inhibitory effect of the N-terminus can be transferred to a heterologous DNA binding domain and is separable from other activities of TTF-I. We show by several methods that TTF-Ip130, the N-terminal domain alone, and fusions of the N-terminus with the DNA binding domain of Oct2.2 form stable oligomers in solution. Thus, in contrast to previous studies suggesting that activation of TTF-I occurs through proteolysis, we demonstrate that full-length TTF-I mediates termination of rDNA transcription in vivo and in vitro and that the oligomerization state of TTF-I may influence its DNA binding activity.